VD_FINDINFO Décision / 2013 / 809 vom 27. September 2013 - VD Tribunal cantonal (2013)
RELIEF, JUGEMENT PAR DÉFAUT, ABSENCE, FAUTE | 368 al. 3 CPP (CH), 369 al. 1 CPP (CH), 369 al. 4 CPP (CH), 36 al. 1 lit. b PPMin, 36 al. 1 lit. c PPMin, 36 PPMin